The rapidly emerging public health threat of rabies in Timor-Leste, 2024–2025 - Machado, Filipe de Neri; Jong, Joanita Bendita da Costa; Gonzaga, Florindo P; da Conceição, Felisiano; Draper, Anthony DK; Pinheiro, Mateus; Bosco Alves dos Santos, Frederico; Soares, Noel Gama; da Silva Marques, Mariano; Mali, Marcelo Amaral; Ximenes Belo, Aloto; da Costa Amaral, Benigna Veneranda; et al. (Western Pacific Surveillance and Response, 2025)
Timor-Leste was rabies-free until March 2024. Since then, detections in dogs and human cases have occurred in a growing number of municipalities. Access to vaccines and rabies immunoglobulin needs to be increased by strengthening vaccine supply, integrating into routine immunization programmes and increasing awareness of the risk of rabies.
Keywords: rabies; Timor-Leste; dog bite; post-exposure prophylaxis; rabies immunoglobulin